The relationship between women's level of knowledge about cancer screenings and health literacy - Uçar, Mehmet; Gül, Ebru (My University, 2024)
This research aimed to investigate the relationship between women's level of knowledge about cancer screenings and health literacy. The research involved a descriptive study design and included 418 women, aged between 18 and 65, who registered at two different Family Health Centers in a provincial center in eastern Türkiye. The research utilized three separate forms to collect the study data: the \"Descriptive Features Form,\" the \"Knowledge Scale for Cancer Screenings,\" and the \"Health Literacy Scale-Short Form.\" The research found the average age of the participants to be 41.88±12.91. In addition, a low level positive relationship was found between the knowledge scale and its sub-dimensions regarding cancer screenings and the health literacy scale (respectively, p<0.05, p<0.001). The research identified a slightly positive relationship between women's knowledge about cancer screenings and health literacy. It also concluded that some sociodemographic characteristics were effective factors in women's cancer screening knowledge and health literacy.
Keywords: Cancer; Knowledge; health literacy; women; cancer screenings